2016
DOI: 10.1007/s12103-015-9321-7
|View full text |Cite
|
Sign up to set email alerts
|

Prosecutors’ Perspectives on Elder Justice Using an Elder Abuse Forensic Center

Abstract: Prosecution is a rare outcome in elder financial exploitation. Previous studies have shown that elder abuse forensic centers—multidisciplinary teams that help investigate and respond to elder mistreatment—increase prosecution rates by enhancing teamwork across agencies. Research is needed to identify what aspects of this intervention model lead to better elder justice outcomes. Six District Attorneys (DAs) were interviewed about their experiences working with other agencies at an elder abuse forensic center (t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Two articles focused on the likelihood of professionals pursuing prosecution of elder abuse perpetrators after participating in MDTs (DeLiema et al, 2016; Gassoumis et al, 2015). Both studies found that participating in MDTs increased the likelihood of prosecuting a case of elder abuse.…”
Section: Resultsmentioning
confidence: 99%
“…Two articles focused on the likelihood of professionals pursuing prosecution of elder abuse perpetrators after participating in MDTs (DeLiema et al, 2016; Gassoumis et al, 2015). Both studies found that participating in MDTs increased the likelihood of prosecuting a case of elder abuse.…”
Section: Resultsmentioning
confidence: 99%
“…In Japan, understanding the role of relevant institutions, including forensic medicine departments, and where to connect cases seems to be important for dealing with elder abuse. As in cases overseas, multidisciplinary teams that include experts in law, medicine and social services [23] might be able to tackle complex problems including family relationships in a comprehensive manner.…”
Section: Forensic Characteristics Of Physical Elder Abusementioning
confidence: 99%
“…In the United States, the Adult Protective Services (APS) agency plays an important role in intervening in cases of elder abuse, and according to Lachs and Pillemer [22], interventions for identified cases are not only tailored to the victim's situation, but also rely heavily on local resources and on family resources and dynamics. Some regions operate forensic centers staffed by multidisciplinary teams that include experts in law, criminal justice, medicine and social welfare [23]. These centers' activities are attracting attention and expanding [24], but no details on the actual state of collaboration between related institutions, including forensic medicine departments, have been reported to date.…”
Section: Introductionmentioning
confidence: 99%